Search for single production of vector-like T quarks decaying into Ht or Zt in pp collisions at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Keywords : Hadron-Hadron Scattering, Vector-Like Quarks.; Springer Open.